Munculnya Resolusi Wha ( World Health Assembly ) No.64/56 Dalam Kerjasama Penanganan Pandemi Influenza Dengan Kerangka Gisrs ( Global In Uenza Surveillance And Respon System ) Who - Dony de Rosari; Asep Saepudin (Jurnal Paradigma, 2013)
Resolution WHA ( World Health Assembly ) No 64/56 Mei 2011, was an International Health Policy which change international mechanism on pandemic in uenza global countermeasures. Before this Resolutian has rati cation as of cial rules for pandemic in uenza countermeasures there was set old mechanism called Global In uenza Surveillance Network ( GISN ). GISN was built in 1952, and had been working more than 60 th, to help people for being handle the humman global disaster cause by in uenza virus. GISN was effectived and ef ciented mechanism to gure out pandemic in uenza case in world. That was be done on coordination, dedication and expertise laboratoris in entire world. This network has be able to continue supervision evolution deployment and in uenza virus distribution. Therefore, GISN cuold be provided timely data and other information, a lot of comperhensive precept, recommendation, and health produce so it is could be fondation for pandemic in uenza preparedeness. Although was a international establishment mechanism , GISN have some weakness that is asked for reformation. GISN didn’t have of cial rules to guard all process of pandemic in uenza countermeasures. This weakness cause many problem where is incur losses devlopment countrys which is near to pandemic in uenza case. Based on that problem Indonesia and other development countrys demand WHO ( World Health Organization ) to change internasional mechanism on pandemic in uenza (GISN ) so be compitable and will be done on three principles ; equity, equality and transparent